Zarządzanie zasobami przestrzeni miasta - ujęcie definicyjne - Rynio, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The goal of city space administration is to realize all the needs of its inhabitants. The main determinant of local space management is the implementation of the idea of balanced development. It is very difficult to reach all elements of balanced development, this is why it is necessary to engage city government and to gain acceptance of inhabitants for undertaken steps towards economic use of city space. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 171-177